Identification of TIFY Family Genes and Analysis of Their Expression Profiles in Response to Phytohormone Treatments and Melampsora larici-populina Infection in Poplar - Xia, Wenxiu; Yu, Hongyan; Cao, Pei; Luo, Jie; Wang, Nian (Frontiers in Plant Science, 2017)
The TIFY domain contains approximately 36 conserved amino acids that form the core motif TIF[F/Y]XG, and they were reported to play important roles in plant growth, tissue development and defence regulation. Moreover, more and more evidence has shown that some members of the TIFY gene family perform their functions by modulating plant hormone signalling pathways. Poplar trees are found worldwide, and they comprise approximately 30 species. Benefit from the importance of poplar and its advanced platform, this tree is considered to be the model perennial plant. Here, we conducted a genome-wide identification of TIFY genes in poplar, and 24 TIFY genes were found. These 24 TIFY genes were assigned to different subfamilies according to the presence or absence of domains and motifs that they harboured. Careful analyses of their locations, structures, evolution and duplication patterns revealed an overview of this gene family in poplar. The expression profiles of these 24 TIFY genes were then analysed in different tissues using publicly available expression data; their expression profiles following different JA/SA treatments and infection with leaf rust pathogen were also carefully examined by qRT-PCR assays. Based on their expression profiles, the functions of a number of TIFY genes could be predicted. By performing this study, we have provided valuable information for further functional characterisation of TIFY genes in poplar and candidate genes for the improvement of poplar disease resistance.